Managerial decision making styles, decision making skills and organizational effectiveness amongst deans of public universities in Malaysia / Leele Susana Jamian - Jamian, Leele Susana (2015)
Decision making holds a fundamental function as it is pivotal in all organizations. Henceforth, quality of decision made often portray the effectiveness of leaders which subsequently affects the effectiveness of the whole organisation. In light of this, the current study aimed to explore the relationship of managerial decision making styles (DMS), decision making skills (DMSKILLS) and organizational effectiveness (OE) among deans of public universities in Malaysia. This study was guided by four research objectives and five research questions. A descriptive-correlational research design employing the mixed-methods approach was used to explore these relationships. Two groups of respondents were involved in the study namely: 54 deans and 716 subordinates from four randomly selected Malaysian public universities. Quantitative data were collected from respondents via survey while qualitative data were collected via open-ended questions and semi-structured interviews. Findings indicated that a majority of deans rated themselves as Behavioural decision-makers and this was corroborated by their subordinates. Secondly, there was a significant difference in the rating of deans and their subordinates with regards to DMSKILLS. The deans rated themselves as possessing high DMSKILLS (M=5.80) whilst their subordinates felt they possessed a moderate to a high frequency level of DMSKILLS (M=4.75). Thirdly, there was also a significant difference in the ratings on OE as the deans (M=5.42) displayed averagely higher mean score than their subordinates (M=4.88). Furthermore the study revealed that there was a significant relationship between deans’ managerial DMS levels and OE. Results via MANOVA analysis indicated that there were patterns of relationships between managerial DMS and OE rated by the subordinates. Deans’ Analytical decision style which embodied the autocratic bent has influenced two OE constructs, namely Professional Development and Quality of the Faculty (PDQF), and Organizational Health (OH). These findings suggested that the more dominant the deans’ Analytical decision style, the more effective the PDQF and OH constructs of the public universities in Malaysia. Lastly, findings revealed that both deans (R=.471) and their subordinates (R=.507) rated the statistical relationship magnitude between DMSKILLS and OE as positive and moderate. In addition, the multivariate regression results by deans implied that 22.2% (R2 =0.222) of the variance in OE score could be predicted from independent variables in DMSKIILS dimensions in comparison to 25.7% (R2 =0.257) by the subordinates. All in all, the study revealed that there were significant relationships of deans’ managerial DMS and DMSKILLS towards OE at the public universities in Malaysia. Hence, all these lead to important implications in the aspect of theoretical and empirical contributions, as well as the methodological, policy and training implications.